Unveiling concentrations of trace elements in the Lower Indus River: risks to aquatic life and human health - Boota, Muhammad Waseem; Soomro, Shan-e-hyder; Xia, Haoming; Qin, Yaochen; Idrees, Muhammad Bilal; Yousaf, Ayesha (Frontiers in Marine Science, 2024)
Concentration of trace elements (CTEs) is a significant environmental concern worldwide. This study assessed CTEs levels in the Lower Indus River (LIR) by analyzing CTEs in water, sediments, tissues of fish (Cirrhinus mrigala), and macrophytes using electrothermal atomic absorption spectrometry (ETAAS) and flame atomic absorption spectrometry (FAAS). The study shows that CTEs range -Arsenic (As, 58.7-112.1 μg/l), lead (Pb, 59.9-95.6 μg/l), Cadmium (Cd, 3.8-8.1 μg/l), nickel (Ni, 40.9-63.4 μg/l), and zinc (Zn, 590.7-847.6 μg/l)and water parameters (temperature, pH, COD, BOD, turbidity, alkalinity) exceeded WHO (2011) acceptable limits. The CTEs (mg/ kg dried basis) were analyzed in fish tissues, and As, Cd, Cr, Cu, Hg, Ni, and Zn have the accumulation order as liver > gill > muscle, respectively. Contrarily, Ag and Pb were present in higher amounts in gills than in the liver (gill > liver > muscle). Prediction of bioavailability of CTEs, with the extraction of sediment load with EDTA, revealed that As, Cd, and Zn were among the most bioavailable elements in the LIR. Health risk assessment indicated that the presence of CTEs in the fish could pose potential adverse health effects on humans. The study emphasizes significant ecological and health concerns due to fish consumption in the affected region, noting high risks of non-carcinogenic effects. These insights are essential for policymakers and stakeholders in Sindh Province to manage and reduce trace element pollution.